Growth behaviour of microbial cells immobilised within hydrogel spheres - Chan, Eng Seng; Pogaku Ravindra (Universiti Malaysia Sabah, 2007)
The effect of immobilization on cell growth in MRS medium and cell survival during exposure to acidic medium were studied in this project. The growth kinetic models of L.casei 01 were developed using initial rate method and Lineweaver-Burke plot. Growth kinetics of immobilized cell was found to follow a competitive model.